2013
DOI: 10.1128/ec.00196-13
|View full text |Cite
|
Sign up to set email alerts
|

Murine Models of Candida Gastrointestinal Colonization and Dissemination

Abstract: Ninety-five percent of infectious agents enter through exposed mucosal surfaces, such as the respiratory and gastrointestinal (GI) tracts. The human GI tract is colonized with trillions of commensal microbes, including numerous Candida spp. Some commensal microbes in the GI tract can cause serious human infections under specific circumstances, typically involving changes in the gut environment and/or host immune conditions. Therefore, utilizing animal models of fungal GI colonization and dissemination can lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 99 publications
(96 reference statements)
2
109
1
Order By: Relevance
“…Mice do not naturally harbor Candida species and require some repression of the natural microbiome to sustain Candida colonization (Koh 2013), while the "natural" gut mycobiome of laboratory mice is strongly influenced by the environment (food source, bedding etc. ; Hallen-Adams pers obs).…”
Section: Discussionmentioning
confidence: 99%
“…Mice do not naturally harbor Candida species and require some repression of the natural microbiome to sustain Candida colonization (Koh 2013), while the "natural" gut mycobiome of laboratory mice is strongly influenced by the environment (food source, bedding etc. ; Hallen-Adams pers obs).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic treatment or the use of germfree gnotobiotic animals enhances consistent colonization of the gut (81). In terms of innate immunity, mice with congenital granulocytic cell deficiencies are susceptible to GI candidiasis but mount C. albicans-specific adaptive responses and eventually clear the infection (106).…”
Section: Non-cd4mentioning
confidence: 99%
“…2D). While this has been demonstrated using murine models (81), monitoring human C. albicans intestinal colonization levels is more problematic. However, more recent clinical studies examining fecal loads have demonstrated increased Candida levels with antibotic treatment (101).…”
Section: Non-cd4mentioning
confidence: 99%
“…In mice, a pioneering study was conducted by Cutler's research group showing that animals fed with antibiotic-containing water were stably colonized by the fungus (60). Other studies have largely confirmed and expanded on the mechanisms of Candida colonization in these mice, with no data reported, however, on vaginal colonization and infection (59,(61)(62)(63). Since antibiotic treatment is a well-known risk factor for vaginal candidiasis in women, this model should be characterized by some level of spontaneous susceptibility to vaginal candidiasis.…”
Section: Conclusion About the Relevance Of Rodent Models To Human DImentioning
confidence: 99%